Low skull bone density is associated with poor motor prognosis in women with Parkinson’s disease - Jeong, Seong Ho; Hong, Namki; Lee, Hye Sun; Han, Sookyeong; Lee, Young-gun; Lee, Yoonju; Rhee, Yumie; Sohn, Young H.; Lee, Phil Hyu (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) and osteoporosis are degenerative diseases that have shared pathomechanisms. To investigate the associations of skull bone density with nigrostriatal dopaminergic degeneration and longitudinal motor prognosis in female patients with PD. We analyzed the data of 260 drug-naïve female PD patients aged ≥50 years old who were followed-up for ≥3 years after their first visit to the clinic with baseline dopamine transporter (DAT) imaging. We measured skull bone density as a surrogate marker for systemic bone loss by calculating the Hounsfield unit (HU) in computed tomography scans. A Cox proportional hazard model was built to compare the rates of levodopa-induced dyskinesia (LID) or wearing-off according to skull HU. Longitudinal changes in levodopa-equivalent dose (LED) during a 3-year follow-up were assessed using a linear mixed model. A lower skull HU was associated with lower baseline DAT availability in striatal subregions; however, this relationship was not significant after adjusting for age, disease duration, body mass index, and white matter hyperintensities. After adjusting for confounding factors, a lower skull HU was significantly associated with an increased risk of LID development (hazard ratio = 1.660 per 1 standard deviation decrease, p = 0.007) and wearing-off (hazard ratio = 1.613, p = 0.016) in younger (<67 years) but not in older patients. Furthermore, a lower skull HU was associated with a steeper increase in LED during follow-up in younger patients only (β = –21.99, p < 0.001). This study suggests that baseline skull bone density would be closely linked to motor prognosis in drug naïve women with PD.